The first palpimanid spiders from Bolivia: two new species of the genus Otiothops MacLeay, and the female of Fernandezina pulchra Birabén (Araneae: Palpimanidae: Otiothopinae) - Piacentini, Luis Norberto (2013)
The araneomorph spider family Palpimanidae is reported from Bolivia for the first time. Two new species: Otiothops kathiae and O. naokii are described and illustrated based on specimens recently collected in Santa Cruz Department. Additionally, Fernandezina pulchra Birabén, 1951 previously known only from Formosa, in northern Argentina, is newly recorded from Santa Cruz, and the female is described for the first time. Potential relationships with previously described species are also briefly discussed.